Polydatin Protects Bone Marrow Stem Cells against Oxidative Injury: Involvement of Nrf 2/ARE Pathways - Meihui Chen; Yu Hou; Dingkun Lin (Stem Cells International)
Polydatin, a glucoside of resveratrol, has been reported to possess potent antioxidative effects. In the present study, we aimed to investigate the effects of polydatin in bone marrow-derived mesenchymal stem cells (BMSCs) death caused by hydrogen peroxide (H2O2), imitating the microenvironment surrounding transplanted cells in the injured spinal cord in vitro. In our study, MTT results showed that polydatin effectively prevented the decrease of cell viability caused by H2O2. Hochest 33258, Annexin V-PI, and Western blot assay showed H2O2-induced apoptosis in BMSCs, which was attenuated by polydatin. Further studies indicated that polydatin significantly protects BMSCs against apoptosis due to its antioxidative effects and the regulation of Nrf 2/ARE pathway. Taken together, our results indicate that polydatin could be used in combination with BMSCs for the treatment of spinal cord injury by improving the cell survival and oxidative stress microenvironments.